Digital Marketing in The Hospital: A Scoping Review - Francesca Chandra, Alexandra; Nadjib, Mardiati (Riviera Publishing, 2023)
Hospitals know smart users better through digital marketing than traditional marketing. The goal of hospital marketing is to assess and understand potential patients' needs and wants so they can meet those needs at the highest level. The Internet, email, and social media are cheaper than direct marketing and can create opportunities to market services to virtual customers, bridge the gap and increase their awareness of the services offered everywhere. This paper aims to determine the effect of digital marketing in hospitals. This scoping review followed a systematic review's study selection process. Relevant studies were collected from Open Knowledge Maps and Google Scholar. The results of this study indicate that some information related to the implementation of digital marketing has challenges. Therefore, there is a need for innovation in implementing digital marketing. In addition, the use of hospital applications can be used in online registration media and media marketing. During the pandemic, hospitals need innovative marketing strategies to attract new patients, expand the business, increase customer trust, and strengthen loyalty. Digital marketing media significantly impact sales promotion, business expansion, and service quality.